An evaluation of different provision strategies for scaled-up container-based sanitation - Charlie Ferguson (IWA Publishing, 2021)
Container-based sanitation (CBS) is increasingly used to provide safely managed sanitation in low-income urban settlements. However, questions remain around the viability of scaling up the technology, partly because it relies on regular emptying and servicing of containers by a CBS provider. This paper investigates mechanisms by which this process can be achieved efficiently. Three separate collection strategies are evaluated for their routing efficiencies as CBS goes to scale. An open-source route optimisation solver determines the constituent driving and walking distances necessary for each strategy and has been applied in areas of Cape Town, Cap-Haïtien, Lima and Nairobi. The results indicate that with fewer users (e.g. 50) transfer station models offer the shortest driving routes. However, these do require users to carry their containers (e.g. up to 170 m when stations are 100 m apart). As the number of users increases (e.g. to 5,000), visiting individual houses from a neighbourhood depot offers increasingly efficient driving distances. Overall, however, the results suggest that economies in collection distances for scaled CBS will be largely conditional on greater vehicle capacity (rather than any particular provision strategy). This highlights the importance of road access throughout low-income urban settlements in providing a viable CBS service at scale. HIGHLIGHTS Container-based sanitation is a form of road-based faecal sludge management.; Efficient routing of collection vehicles is critical for enabling scaled CBS.; This modelling evaluates three existing provision strategies using Google-OR tools.; Transfer stations and depots within neighbourhoods can reduce the required driving.; However, enlarged vehicle capacity offers greatest reductions in collection routing.;